Meningkatkan Hasil Belajar Siswa Menggunakan Media Benda Konkret pada Materi Pecahan Senilai di Kelas IV SDN 2 Kersaratu - Diki Wahyudi; Akhmad Nugraha; Dina Syaflita (Indonesian Journal of Integrated Science and Learning, 2023)
This study aims to improve student learning outcomes on equivalent fraction material in class IV SDN 2 Kersaratu by using concrete objects as media. The subjects in this action research were fourth grade students consisting of 4 male students and 3 female students. Data collection techniques are carried out through four stages, namely: (a) action planning; (b) implementation of actions; (c) observing actions; and (d) reflection. The research was conducted in three improvement cycles. The results of this action research show that student learning outcomes increase after learning is carried out using concrete object media. In cycle 1, only 2 students passed with a percentage of 28.57%. In cycle 2, the number of students who passed increased to 4 students with a percentage of 57.14%. In cycle 3, as many as 6 students completed with a percentage of 85.72%. The use of concrete object media effectively really helps students in understanding fractional material worth in this study. Thus, it is suggested to fourth grade teachers at SDN 2 Kersaratu to use concrete object media in learning this material in order to improve student learning outcomes.